2011
DOI: 10.4161/spmg.1.3.17998
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the assembly of a functional blood-testis barrier in developing rat testes

Abstract: the blood-testis barrier (BtB) is an important ultrastructure in the seminiferous tubule of the mammalian testis that segregates the events of spermatogenesis, in particular post-meiotic germ cell development, from the harmful substances in the environment including toxicants and drugs, as well as from the unwanted hormones and biomolecules in the systemic circulation. It is known that the BtB is assembled by ~15-21 days postpartum (dpp) in rats coinciding with the onset of late cell cycle progression, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Based on the findings reported herein, although the TJ permeability barrier at the BTB after P-glycoprotein knockdown was transiently disrupted as a result of TJ protein redistribution at the BTB, the basal ES proteins N-cadherin and β-catenin, which are capable of conferring the immunological barrier, were unaffected (25). This latter finding explains the maintenance of fertility in mdr1 −/− mice (22,23), and it is also consistent with a recent study showing that an intact BTB is necessary for spermatogonial stem cell differentiation beyond type A spermatogonia to initiate spermatogenesis (26). Additionally, other efflux drug transporters that are also present in Sertoli cells (9) (SI Discussion) can likely supersede the lost function of P-glycoprotein at the BTB in the mdr1 −/− mice.…”
Section: P-glycoprotein Knockdown In Sertoli Cell Epithelium Modulatessupporting
confidence: 78%
“…Based on the findings reported herein, although the TJ permeability barrier at the BTB after P-glycoprotein knockdown was transiently disrupted as a result of TJ protein redistribution at the BTB, the basal ES proteins N-cadherin and β-catenin, which are capable of conferring the immunological barrier, were unaffected (25). This latter finding explains the maintenance of fertility in mdr1 −/− mice (22,23), and it is also consistent with a recent study showing that an intact BTB is necessary for spermatogonial stem cell differentiation beyond type A spermatogonia to initiate spermatogenesis (26). Additionally, other efflux drug transporters that are also present in Sertoli cells (9) (SI Discussion) can likely supersede the lost function of P-glycoprotein at the BTB in the mdr1 −/− mice.…”
Section: P-glycoprotein Knockdown In Sertoli Cell Epithelium Modulatessupporting
confidence: 78%
“…However, a functional BTB is not fully established until 25 dpp. This phenomenon is closely associated with the onset of meiosis I and II (Mok et al 2011). At around 60 dpp, rats are in late puberty (Stumpp et al 2006) when spermatozoa begin to be found in the epididymis (Robb et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…They separate the seminiferous epithelium into a basal and an adluminal compartment through the formation of the blood-testis barrier (BTB) that is located around the basal third of the seminiferous tubule. This barrier is established through tight, adherens and gap junction proteins that form the so called SC-SC junctional complex with gap junctions being believed to play a vital role in its formation and dynamic regulation (Pelletier 1995, Cyr et al 1999, Mok et al 2011, Gerber et al 2014, Jiang et al 2014, Gerber 2015, Rode et al 2015.…”
mentioning
confidence: 99%